Potential of Marine Macroalgae in Stabilizing Bio-Fabricated Nanoparticles for Photodegradation Application: A Review - Ramadhani, Ramadhani; Said, Ahmad (CONSERVA, 2024)
Marine macroalgae, or seaweeds, have emerged as promising sources for the green synthesis and stabilization of nanoparticles, offering remarkable potential in photodegradation processes. These abundant and renewable resources harbor a diverse array of bioactive compounds, including polysaccharides, proteins, flavonoid, and pigments, which can act as reducing, capping, and stabilizing agents. The integration of macroalgae-derived stabilizing agents into nanoparticle synthesis confers unique properties, enhancing photocatalytic performance and stability. This review comprehensively examines the role of marine macroalgae as stabilizing agents for bio-fabricated nanoparticles in photodegradation applications in particular for toxic azo dye degradation and organic compounds. It explores into the mechanisms of nanoparticle synthesis and stabilization, explores the diverse macroalgal species employed, and evaluates their photocatalytic efficiency against various organic and inorganic pollutants in wastewater. Furthermore, the review critically analyzes the challenges and future perspectives in this field, offering insights into the development of green, sustainable, and efficient remediation strategies for environmental contaminants.